THE DEVELOPMENT OF TOPSIS METHOD ON SPACE MATRIX QUADRAN SWOT ANALYSIS USED TO DETERMINE THE STRATEGY PRIORITY IN AN ATTEMP TO OVERCOME LAND PROBLEM (Case Study : TPU Sumur Batu, Kota Bekasi) - YULIANANDHA MABRUR (NIM: 95114002), ADKHA
SWOT Analysis and TOPSIS method are methods in the decision-making system or Multi-Criteria Decision Making (MCDM). TOPSIS method holds the key of strategic priorities of the strategies that have been prepared using SWOT analysis based on the weight and the rating given appropriate consideration to the land problems. In this case the Problem Tree Analysis is used as a method to describe the land problems, then the results are organized as SWOT strategies by considering Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE). The results of SWOT as criteria for priority level will be determined by using TOPSIS method based on the shortest distance to the Positive Idea Solution (PIS) and the farthest distance of the Negative Idea Solution (NIS). The end result of this research is a priority strategy in dealing with land issues. In accordance with the value of the SWOT analysis, the value of IFE matrix and EFE matrix indicates the position in quadrant IV (defensive), it mean strategy used is WT (Weakness-Threat) strategy. The value of TOPSIS method indicates that the strategy selected priority is WT3 strategy. Based on the results generated priority strategies that incorporation of SWOT analysis and TOPSIS method can provide strategies as the solutions to solve the land problems through the program plan and recommendation.